Spinning Wheels of Knowledge: Elevating Arabic Language Learning Through Innovative Teaching Methods - Puspitasari, Andriyani; Ali Murtadho, Qolbi Zuhri (Universitas Muhammadiyah Surakarta, 2023)
This research explains the application of the Spinning Wheel media or learning tools in English in Arabic language learning, namely as an innovative teaching method to improve students' ability to understand Arabic language material. Teaching media: The Spinning Wheel This is in the shape of a circle and contains an image that then rotates and moves until it stops at one part of the image, which shows the content of the message or information in the form of the subject to be conveyed. This research aims to increase students' understanding of the vocabulary in the material and also improve student learning outcomes. In this research, students were divided into four groups and given the task of answering the questions listed on the spinning wheel, such as vocabulary questions and texts taken from the material. From the application results, researchers have found that this history-spinning wheel teaching media can increase student activity and learning outcomes. Apart from that, this media makes the class come alive, and students are enthusiastic about participating in learning, with various elements and interesting variations in this media. However, this research also identified several challenges in planning and implementation, such as designing and following instructions appropriate to learning and updating assessment evaluations. Nevertheless, the findings from this research provide the basis for considering the use of the historical rotating wheel teaching media as a creative, orderly, neat, and reasonable approach to improving Arabic language learning outcomes.